Song Repertoire of the Crimean Chaffinch, Fringilla coelebs (Fringillidae), and Comparative Analysis of the Vocalization Features of F. c. solomkoi, F. c. coelebs and F. c. caucasica Subspecies - Tsvelykh, A.N.; Yablonovska-Grishchenko, E.D. (Вестник зоологии, 2012)
Song repertoire of chaffinch F. c. solomkoi subspecies from Crimea was analyzed. We discerned 38 song types in Crimean chaffinches’ repertoire, 27 of them were more frequent. Comparing Crimean chaffinches’ songs with those of nominative subspecies from Eastern Europe showed no common songs. Comparison of individual song elements showed that songs of F. c. solomkoi consisted of 108 elements, of which 18 were distinctive to Crimean birds, 18 were specific to Crimean chaffinches and Carpa-thian F. c. coelebs population while absent in songs of chaffinches from Eastern Europe plains. Comparison of F. c. solomkoi songs with songs of Caucasian subspecies F. c. caucasica revealed no common types of songs. There are certain similarities in song structures between some Crimean chaffinches and hybrid popula-tion of F. c. caucasica and F. c. solomkoi from Northwest Caucasus. Other specifics of vocalization showed drastic differences in rain-call structures of all subspecies and no after-song “kit“ element for Caucasian sub-species. Проанализирован песенный репертуар зябликов подвида F. c. solomkoi, населяющих Крымские горы. В репертуаре зябликов Крыма выявлено 38 типов песен, из которых наиболее распространены 27. Сравнение песен крымских зябликов с песнями птиц номинативного подвида из Восточной Европы показало полное отсутствие общих для обоих подвидов типов песен. При сравнении отдельных элементов песен из 108 элементов, выявленных в песнях F. c. solomkoi, 18 оказались специфичными для крымских птиц, еще 18 элементов — общими с элементами, выявленными исключительно у популяции F. c. coelebs Карпат и отсутствующих в песнях зябликов из равнинных районов Восточной Европы. Сравнение песен F. c. solomkoi с песнями птиц кавказского подвида F. c. caucasica также показало отсутствие общих типов песен. Отмечено определённое сходство в структуре некоторых песен зябликов крымской популяции и птиц из Северо-Западного Кавказа, населённого гибридной популяцией F. c. caucasica и F. c. solomkoi. Сравнение других особенностей вокализации демонстрирует радикальные отличия в структуре «дождевого сигнала» между всеми исследованными подвидами и отсутствие исполнения послепесенного элемента «kit» птицами кавказского подвида.